Strategies to Increase Customer Loyalty on Brands (Case Study on Nayam Brand on Grabfood) - Ridho Febrianto Wibowo (Riviera Publishing, 2024)
The use of technology in business is often utilized as a strategy to obtain information related to marketing, sales, and consumer interest. This study aims to analyze the effect of service quality, product quality, relationship marketing, and consumer satisfaction on consumer loyalty of the Nayam brand on the Grabfood platform. Previous research has examined the relationship between these factors, but this study provides a more comprehensive understanding by integrating them in the context of the online food delivery industry. This study utilizes a causal research design to identify causal relationships between variables. Data collection methods include literature studies, field surveys, and questionnaires. The operational variables are service quality, product quality, relationship marketing, customer satisfaction, and customer loyalty. Sampling was conducted using consecutive sampling with a total of 110 respondents in the Jabodetabek area who had ordered Nayam using the Grabfood food delivery service. Data analysis was conducted using PLS-SEM and SWOT analysis. The results showed that customer satisfaction and product quality have an influence on customer loyalty. On the other hand, service quality has an influence on customer satisfaction. Relationship marketing was found to have an indirect positive influence in building relationships between owners and customers. The findings of this study make a practical contribution to business owners by offering a better understanding of how to retain existing customers, increase revenue, improve marketing efficiency, build a good brand reputation, and create a competitive advantage in the market. From a theoretical perspective, this study contributes to the development of a scientific understanding of customer behavior, the factors that influence it, and its impact on business success.